Green Design, Materials and Manufacturing Processes 2013
DOI: 10.1201/b15002-37
|View full text |Cite
|
Sign up to set email alerts
|

Environmental aspects of lightweight construction in mobility and manufacturing

Abstract: In automotive, mechanical, medical and plant engineering, and the construction industry, lightweight construction is considered one of the most important future technologies, providing good market opportunities for small and medium-sized companies. Due to the increasing relevance of energy and resource efficiency, not only technical and economic, but also environmental aspects have to be considered when assessing lightweight construction. Only with the consideration of environmental and economic aspects modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The first question that guided the extraction of information was how CFRPs perform compared with conventional materials. For this comparison, the system boundaries and functional units, as given in the original work, were kept to allow for comparisons between replacing conventional materials with CFRP in both lightweighting (Albrecht et al (2013); Das (2011); Khalil (2017); Kim (2015); Overly et al (2002); Suzuki et al (2003); Suzuki and Takahashi (2005a); Witik (2011)) and reinforcement (Hofstätter (2017) and Zhou (2013)) applications.…”
Section: Comparison Of Cfrps With Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first question that guided the extraction of information was how CFRPs perform compared with conventional materials. For this comparison, the system boundaries and functional units, as given in the original work, were kept to allow for comparisons between replacing conventional materials with CFRP in both lightweighting (Albrecht et al (2013); Das (2011); Khalil (2017); Kim (2015); Overly et al (2002); Suzuki et al (2003); Suzuki and Takahashi (2005a); Witik (2011)) and reinforcement (Hofstätter (2017) and Zhou (2013)) applications.…”
Section: Comparison Of Cfrps With Other Materialsmentioning
confidence: 99%
“…Studies that were found to deal exclusively with the end-of-life of CFRP (including recycling) are shown in Figure 5. One of the studies presents an average of four values but for the same type of end-of-life activity (Albrecht et al, 2013). Note that the Y-axis has been cut off for some studies.…”
Section: End-of-life Activitiesmentioning
confidence: 99%
“…To the best of our knowledge, no study on S‐LCA exists. For LCA, most cases refer to automotive or railway lightweight design using thermoplastics, that is, carbon fiber reinforced plastics (CFRPs) 31–33 . Four studies come closest to our research objectives: Williams Portal et al 34 investigated various reinforcement technologies for façade elements, among others also SRC and CCC.…”
Section: Introductionmentioning
confidence: 99%
“…For LCA, most cases refer to automotive or railway lightweight design using thermoplastics, that is, carbon fiber reinforced plastics (CFRPs). [31][32][33] Four studies come closest to our research objectives: Williams Portal et al 34 investigated various reinforcement technologies for façade elements, among others also SRC and CCC. CCC yielded the lowest total environmental impacts when compared by means of cradle-to-gate LCA.…”
mentioning
confidence: 99%
“…1,2 Advantages of lightweight design include the legally required reduction of CO 2 emissions, enhanced driving performance or higher payload. 1,[3][4][5] Fibre-reinforced plastics (FRPs) are particularly well suited for lightweight design because of their excellent mechanical properties with respect to their density. 6 Furthermore, the anisotropy of FRPs makes it possible to tailor strength and stiffness along load paths to achieve desired overall structural properties.…”
Section: Introductionmentioning
confidence: 99%